Deciphering Resistome and Virulome Diversity in a Porcine Slaughterhouse and Pork Products Through Its Production Chain - Campos Calero, Guillermo; Caballero Gómez, Natacha; Benomar, Nabil; Pérez Montoro, Beatriz; Knapp, Charles W.; Gálvez, Antonio; Abriouel, Hikmate (Frontiers in Microbiology, 2018)
We aimed to better understand resistome and virulome patterns on animal and process-area surfaces through a pig slaughterhouse to track possible contamination within the food production chain. Culture-dependent methods revealed high levels of microbial contamination, corresponding to mesophilic and pathogenic bacteria on both the animal and process-area surfaces mainly in the anesthesia (AA and AS) zone followed by “scorching & whip” (FA and FS) zone and also in the end products. To evaluate the potential risk of antibiotic resistance and virulence determinants, shotgun metagenomic DNA-sequencing of isolates from selected areas/products uncovered a high diversity and richness of antibiotic resistance genes (ARGs): 55-62 genes in the anesthesia area (AA and AS) and 35-40 in “animal-arrival zone” (MA and MS). The “scorching & whip” (FA and FS) area, however, exhibited lowered abundance of ARGs (1-6), indicating that the scalding and depilating process (an intermediate zone between “anesthesia” and “scorching & whip”) significantly decreased bacterial load by 1-3 log10 but also diminished the resistome. The high prevalence of antibiotic-inactivating enzyme genes in the “animal-arrival zone” (60-65%) and “anesthesia” area (56%) were mainly represented by those for aminoglycoside (46-51%) and lincosamide (14-19%) resistance, which did not reflect selective pressures by antibiotics most commonly used in pig therapy—tetracyclines and beta-lactams. Contrary to ARGs, greater number of virulence resistance genes were detected after evisceration in some products such as kidney, which reflected the poor hygienic practices. More than 19 general virulence features—mainly adherence, secretion system, chemotaxis and motility, invasion and motility were detected in some products. However, immune evasion determinants were detected in almost all samples analyzed from the begining of the process, with highest amounts found from the anesthesia area. We conclude that there are two main sources of contamination in a pig slaughterhouse: the microorganisms carried on the animals’ hide, and those from the evisceration step. As such, focussing control measures, e.g., enhanced disinfection procedures, on these contamination-source areas may reduce risks to food safety and consumer health, since the antibiotic and virulence determinants may spread to end products and the environment; further, ARG and virulence traits can exacerbate pathogen treatments.